Split ring aperture for optical magnetic field enhancement by radially polarized beam - Yang, Y. (2013)
Inspired by Babinet’s principle, we proposed a new plasmonic structure for enhancing the optical magnetic field, i.e. split ring aperture, whose complement is the well-known split ring. The split ring aperture exhibits a much better performance under radially polarized excitation than linearly polarized excitation. We attribute the ultra-high intensity enhancement in magnetic field to the symmetric matching between the aperture geometry and the direction of the electric field vector in each direction of radially excitation. The impact of the design parameters on the intensity enhancement and resonant wavelength is also investigated in details.